(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Wood veneer is mainly used for interior decoration applications in many different segments. It's ideal for residential projects, hotel projects, offices giving to the any interior a unique look and feel. In addition, veneer is also processed to create a variety of products such as veneer parquet, flexible veneer sheets, wood veneer boards, wood veneer wallpaper, etc. From the other side, veneered surfaces will always to a greater or lesser degree could change color, particular upon exposure to natural and artificial light. The degree of color change will depend on such factors as the species chosen, the coating type used and intensity and period of the exposure to light. In addition, conventional finishes have a tendency to yellow with age which can have quite dramatic effects on the original color of the selected timber. To minimize these effects new finishes have to be developed. In the paper new, unvisible nanolevel coating for veneer finish based on the sol-gel process is offered. It is known that the sol–gel technique is an established industrial process for the generation of colloidal nanoparticles from liquid phase, which has been further developed in last years for the production of advanced coatings. It is well adapted for oxide nanoparticles and composites synthesis. The main advantages of sol-gel techniques are comparable low processing temperatures offering unique opportunities for access to organic and inorganic materials. The sol synthesis and application technology as well protective properties of coating will be discussed.